2016
DOI: 10.1515/aep-2016-0042
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the potential of fungal-bacterial consortium for low-cost biodegradation and detoxification of textile effluent

Abstract: Abstract:In the present study, the enrichment and isolation of textile effl uent decolorizing bacteria were carried out in wheat bran (WB) medium. The isolated bacterium Providencia rettgeri strain HSL1 was then tested for decolorization of textile effl uent in consortium with a dyestuff degrading fungus Aspergillus ochraceus NCIM 1146. Decolorization study suggests that A. ochraceus NCIM 1146 and P. rettgeri strain HSL1 alone re moves only 6 and 32% of textile effl uent American Dye Manufacturing Institute re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 37 publications
(50 reference statements)
0
7
0
Order By: Relevance
“…The use of fungal-bacterial co-cultures has been shown to enhance the decolorization of various synthetic dyes compared to their monocultures [23,60,73,[78][79][80][81][82][83] (Table 1). Most of the published studies used synthetic wastewater containing single dyes [60,73,78,[81][82][83],…”
Section: Synthetic Dyesmentioning
confidence: 99%
“…The use of fungal-bacterial co-cultures has been shown to enhance the decolorization of various synthetic dyes compared to their monocultures [23,60,73,[78][79][80][81][82][83] (Table 1). Most of the published studies used synthetic wastewater containing single dyes [60,73,78,[81][82][83],…”
Section: Synthetic Dyesmentioning
confidence: 99%
“…Some reports indicated that fungi-bacteria co-cultures showed higher efficiency and stability [111][112][113][114] to degrade the mixture of many kinds of macromolecule organics into small-molecule substances which can be further degraded or even mineralized by bacteria. 65,115 In addition, few studies illustrate the ability of bacterium yeast consortium to treat TWWs. 116 Apart from these approaches, A synergistic strategy occurred by involving plants such a plant-bacterial system using Glandularia pulchella and Pseudomonas monteilii ANK 117 or plant consortia.…”
Section: Other Microbial Consortiamentioning
confidence: 99%
“…Retention time of each compound depends upon their affi nity towards column as well as the mobile phase used for elution (Iqbal and Asgher 2013, Sadhasivam et al 2008). The formation of multiple peaks in treated samples at different time than in an untreated sample confi rms the biodegradation of effl uents (Lade et al 2016).…”
Section: Hplc Analysis Of Bio-treated Industrial Effl Uentsmentioning
confidence: 99%